Difference of opinions amongst the neo jurists of the Shafi’i is School of thought and its factors: A descriptive and analytical study / Ali Zeinelabdin Elhusseini Sayed Ahmed Zayed - Ali Zeinelabdin Elhusseini , Sayed Ahmed Zayed (2019)
This research deals with a jurisprudential issue that pertains to scholars differing in opinions within the Shafi’ school of thought with special focus on the recent or neo jurists of the said school as a subject matter since this contention interestingly manifests itself in different many ways and also since most of these jurists follow the same Imam (the founder of the Shafi’i school of thought). This research aims to explain the factors that have contributed to the Shafi’ school of thought gaining currency and popularity by highlighting its characteristics. In addition, it aims to shed light on the term khilaf (differing in opinion on an issue related to jurisprudence) and its historical development in the Shafi’ school of thought as well as the efforts exerted by recent or neo jurists in serving and expounding this school of thought. That is, it provides an overview about the stages of khilaf that occurred among the recent jurists of the school at hand with special focus on the causes of khilaf through practical examples. This research uses a historiographical approach in accounting for the phenomenon of Khilafiah in the school of thought mentioned above. It uses an inductive approach to conclude some examples meant to make the causes and results clear and understandable. It uses an analytical approach to extrapolate some cases revealing the causes of the khilaf that happened among the neo jurists of the school. Moreover, it uses a descriptive approach aimed at overviewing the subject matter of the research and at describing khilaf and issues related to it. Finally, the research has concluded: that Shafi’ school of thought has its own characteristics that are partly attributed to the personality of al-Imam al- Shafi’i himself on the one hand, and partly something that has to do with the school itself on the other. That is, there is no any distinction made in the school between khilaf and ikhtilaf. In this context, a juristic statement is treated as invalid by way of unifying the four schools of thought into one school. Likewise, the neo jurists of the Shafi’ school of thought use the term ‘consideration of khilaf’ to mean avoiding ikhtilaf. They have also included among the conflicting jurisprudential issues some debates ascribed to al-Imam al-Shafi’i. In other words, khilaf, according to the Shafi’ school of thought is classified into five categories: starting with khilaf as understood by al-Imam al- Shafi’ and ending with khilaf as understood by the neo jurists. Six attributes were ascribed to the jurists who have their own independent views explicit in the textbooks used in the school. It is also explicit that the term coined by the neo jurists has gradually developed and has gained currency. In fact, it has undergone some changes at every stage. They used the term al-Mutaqaddimin (the earlier jurists) to refer to the period before al-Sheikh Zakariyya al-Ansari, and the term al-Muta’akhkhirin (the recent jurists) to refer to his period and that after him. The efforts exerted by the recent jurists to serve the school have been manifold and plenty of variety. Furthermore, this service ranges between writing textbooks, interpretations or commentaries. This service also has extended to include improbable unfounded predictions and highly probable hypotheses in which they would issue a ruling and a verdict vis-à-vis that specific hypothetically-based case. The recent jurists of the Shafi’i school of thought are classified into those concerned with expounding textbooks and those concerned with writing commentaries. There is no significant distinction between the period of those concerned with expounding the text books and those concerned with the commentaries. khilaf is classified into three categories in the view of the recent jurists. They have actually coined their own theoretical framework. Authorship or writing on the issues of khilaf has undergone two phases. There are three main causes that bring about khilaf : first, khilaf can happen as a result of narration, and this includes differing over what is stated by al-Rafi'i and al-Nawawi, and differing over what is stated by al-Shafi’i as well as what is said by other scholars within the same school of thought. In addition, the prolific writings by both Ibn Hajar and al-Ramli and different versions of commentaries are equally a source of difference of opinion; second, khilaf can occur as a result of reasoning and adjusting. In other words, khilaf may happen because of unsound reasoning and analysis; similarly, it may occur as a result its compliance with a customary law, or because of a shortcoming in a particular statement, or even due to khilaf that originally resulted out of another khilaf; third, there is khilaf that happens as a result of jurisprudential rules, or because of different conditions and parameters, or as a result of pressing and new issues, or as a result of irregularities and anomalies.